A Quality of Growth Index: Evidence from Indian States. (March 2016) - Ghosh, Saibal
Employing decadal data for the period 1971–2011, this article constructs a quality of growth index (QGI) for major Indian states. The index encompasses not only growth and its durability, but also encompasses several relevant social dimensions. These include variables such as stability and diversification of growth as well as institutional quality and social indicators such as life expectancy and literacy rate. The extended period chosen enables us to trace the evolution of the index over a sufficiently long period of time. Several findings stand out. First, the average value of the index is higher in the post-reform period, suggesting that there has been an overall improvement in the quality of growth over time. However, although the BIMAROU states have raised their QGI, they have still lagged behind their peers. Second, it is typically the industrialized states which have witnessed higher QGI. And third, the industrialized states, with improved financial access and better physical infrastructure, which are better placed are those with higher QGI.